Don't say a word - Milchan, Arnon; Kopelson, Arnold; Kopelson, Anne; Peckham, Anthony; Kelly, Patrick Smith; Fleder, Gary; Douglas, Michael, 1944-; Bean, Sean; Murphy, Brittany; McCole Bartusiak, Skye, 1992-2014; Torry, Guy; Esposito, Jennifer, 1972-; et al. ([United States] : Twentieth Century Fox Home Entertainment, 2001)
When the daughter of a prominent New York psychiatrist is kidnapped, his only hope for her safe return is to pry a 6-digit number from the memory of a troubled teenage girl--and time is running out.
Based on the book by Andrew Klavan.
Originally released as a motion picture in 2001.
Special features: Commentaries by Michael Douglas, Sean Bean, Brittany Murphy, Famke Janssen, Oliver Platt; Director's commentary; Deleted scenes; "Making of" featurette; Set tour featurette; Film scoring featurette; screening room dailies; Brittany Murphy screen test; Storyboard-to-Screen comparisons; Cast/crew bios.
Title from container.
Not viewed.
Sources used: Copyright catalog online; Internet movie database WWW site, viewed 2010-08-11.
Keywords: Psychiatrists -- New York (State) -- Drama; Kidnapping -- New York (State) -- Drama; Feature films; Fiction films; Thrillers (Motion pictures)